2015
DOI: 10.1089/scd.2014.0210
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Suppresses Maintenance of Stemness by Augmenting Proteosomal Degradation of Epidermal Growth Factor Receptor/Epidermal Growth Factor Receptor Variant III in Glioma Stem Cells

Abstract: There is a growing body of evidence that small subpopulations of cells with stem cell-like characteristics within most solid tumors are responsible for the malignancy of aggressive cancer cells and that targeting these cells might be a good therapeutic strategy to reduce the risk of tumor relapse after therapy. Here, we examined the effects of emodin (1,3,8-trihydroxy-6-methylanthraquinone), an active component of the root and rhizome of Rheum palmatum that has several biological activities, including antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 49 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…Tomek et al (9) reported that inhibiting FASN with C75 results in the accumulation of ubiquitinated proteins, including PI3K and MAPK signaling proteins, in ovarian cancer (9). Emodin also induces the proteosomal degradation of EGFR/EGFR variant III in glioma stem cells (41). However, no previous study has reported that emodin induces the degradation of FASN protein.…”
Section: Discussionmentioning
confidence: 99%
“…Tomek et al (9) reported that inhibiting FASN with C75 results in the accumulation of ubiquitinated proteins, including PI3K and MAPK signaling proteins, in ovarian cancer (9). Emodin also induces the proteosomal degradation of EGFR/EGFR variant III in glioma stem cells (41). However, no previous study has reported that emodin induces the degradation of FASN protein.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HSP90 promotes multicell spheroid formation, migration, and invasion of thyroid CSCs, and those CSC phenotype-related activities were sensitive to HSP90 inhibitors [74]. It was demonstrated on cultured glioma SCs that the association of HSP90 with EGFR/EGFRvIII preserves the receptor complexes from proteasomal degradation, thus supporting the work of cancer stemness-promoting pathways [75]. Under conditions of hypoxia and acidosis in the microenvironment of gliomas, tumorous (intracellular) HSP90 was upregulated in the hypoxic niches, which was correlated with both the CSC phenotype's expression and HSP90-dependent HIF upregulation [76].…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoning mentioning
confidence: 94%
“…Emodin effectively blocked the self‐renewal activity of glioma stem cells by suppressing crucial stemness signalling pathways involving Notch‐1, b‐catenin and STAT3. Emodin induced proteosomal degradation of EGFR/EGFRvIII by interfering with its association with Hsp90, leading to partial induction of apoptosis and sensitization of glioma stem cells to ionizing radiation (Kim et al ., ). Wang et al reported that emodin inhibited human cervical cancer HeLa cell proliferation by inducing apoptosis through the intrinsic mitochondrial and extrinsic death receptor pathways (Wang et al ., ).…”
Section: Pharmacologymentioning
confidence: 97%